PRINSIP INTEGRITAS BERDASARKAN INJIL MATIUS 5:17-48 DAN IMPLEMENTASINYA BAGI PELAYAN TUHAN MASAKINI - Manase Gulo (Manna Rafflesia, 2017)
Study of Integrity is a very important word, understood and owned by God's servants in the ministry. Today there are many servants of the Lord who carry out the ministry for mere words, but what has been said is not in accordance with daily behavior. As servants of God must have integrity, but in reality today there are still many servants of God who do not yet have integrity. For example, negating some of God's teachings, not living right before God, swearing false (not honest), and not loving the enemy. Therefore it is very important for every servant of God to have integrity. So in this discussion the writer will explain about the integrity of God's servants in service based on Matthew 5: 17-48, which aims to open the understanding of each servant of God about the attitude that must be held by every servant of God in carrying out their ministry.